2001
DOI: 10.1159/000050348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Fluorosis in Disabled Children and Young Adults in Kuwait

Abstract: Objective: The aim of this study was to determine the prevalence of dental fluorosis in disabled subjects attending the special needs schools in Kuwait. Methods: Eight hundred and thirty-two subjects (442 males, and 390 females) aged 3–29 years, who were visually or hearing impaired or who had physical or developmental disorders, were included in the study. The mean age of the subjects was 12.1 years. The subjects were examined for dental fluorosis using WHO criteria. Dental fluorosis was scored according to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
5
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 10 publications
7
78
5
13
Order By: Relevance
“…A experiência de cárie dentária em pacientes portadores de deficiência tem sido relatada como maior do que a encontrada na população, havendo a necessidade de se estabelecerem programas específicos preventivos e curativos para os pacientes Portadores de Necessidades Especiais 15 . Em seu estudo sobre a prevalência da cárie dentária, Santos et al 16 verificaram um maior CPO-D em crianças com necessidades especiais do que em crianças sem deficiência, devido, principalmente, à dificuldade de manutenção de uma higiene bucal satisfatória.…”
Section: Discussionunclassified
“…A experiência de cárie dentária em pacientes portadores de deficiência tem sido relatada como maior do que a encontrada na população, havendo a necessidade de se estabelecerem programas específicos preventivos e curativos para os pacientes Portadores de Necessidades Especiais 15 . Em seu estudo sobre a prevalência da cárie dentária, Santos et al 16 verificaram um maior CPO-D em crianças com necessidades especiais do que em crianças sem deficiência, devido, principalmente, à dificuldade de manutenção de uma higiene bucal satisfatória.…”
Section: Discussionunclassified
“…The prevalence and severity of oral disease among this group are higher when compared to the general population [17]. Poor periodontal health and oral cleanliness have been observed in children with OFC [21][22][23][24]. These results may be due to low physical abilities, consequent difficulties in tooth brushing, limited understanding on the importance of oral health management [25], difficulties in communicating oral health needs [26] and fear of oral health procedures [27].…”
Section: Resultsmentioning
confidence: 99%
“…[ there is no difference in risk compared with the general population. Some reports concluded that DS population are with higher caries prevalence, [27,28] while others concluded that there is no difference in caries prevalence compared to healthy groups. [29][30][31][32][33] However, most investigators have found a lower prevalence of caries in DS patients in both dentitions.…”
Section: Sexual Developmentmentioning
confidence: 99%